A checklist of angiospermic flora of Lalmai Hills, Comilla, Bangladesh - Hossain, Md Munir; Hassan, Md Abul; Uddin, Mohammad Zashim (Bangladesh Journal of Plant Taxonomy, 2005)
The paper includes a checklist containing a total of 151 angiospermic species (127 dicot and 24 monocot) growing in the Lalmai hills, Comilla, Bangladesh, which has been prepared after the survey of the area during the years 2001 and 2002. Key words Preliminary checklist, angiospermic flora, Lalmai hills, Comilla, Bangladesh DOI: 10.3329/bjpt.v12i2.605 Bangladesh J. Plant Taxon. 12(2): 85-96, 2005 (December)